Penerapan Layanan E-Commerce terhadap Pola Pembelian Barang Elektronik pada Toko Ichtiar Jaya - saputra, mahmuda; dewi, ratna (Universitas Gajah Putih, 2026)
This study aims to analyze the effect of e-commerce service implementation on the purchasing patterns of electronic goods at Ichtiar Jaya Store. The research employs a quantitative approach with data collected through questionnaires distributed to 80 respondents who have experience using e-commerce services. Data analysis was conducted using descriptive statistics and simple linear regression. The results indicate that the implementation of e-commerce is categorized as good, with an average score of 4.10, while consumer purchasing patterns have an average score of 4.08. The regression analysis shows that e-commerce has a positive and significant effect on purchasing patterns, with a regression coefficient of 0.68 and a significance value of less than 0.05. The coefficient of determination (R²) of 62% indicates that most changes in purchasing patterns are influenced by e-commerce services. This study concludes that e-commerce enhances transaction efficiency and shifts consumer behavior toward more active and digitally driven purchasing decisions.